2020
DOI: 10.1038/s42003-020-0808-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating cone photoreceptor development using patient-derived NRL null retinal organoids

Abstract: Photoreceptor loss is a leading cause of blindness, but mechanisms underlying photoreceptor degeneration are not well understood. Treatment strategies would benefit from improved understanding of gene-expression patterns directing photoreceptor development, as many genes are implicated in both development and degeneration. Neural retina leucine zipper (NRL) is critical for rod photoreceptor genesis and degeneration, with NRL mutations known to cause enhanced S-cone syndrome and retinitis pigmentosa. While muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 48 publications
1
67
1
1
Order By: Relevance
“…Note that although rhodopsin was detected in our mutant retinal sections, it may not indicate the presence of fully differentiated rods. Some authors have reported a rod/cone intermediate population, such "cods" have been recently characterized in retinal organoids from a NRL null patient showing an ESCS phenotype (Kallman et al, 2020). The observed phenotype of the D27 mutant could be the result of the short isoform overexpression plus the incapability of the long isoform to dimerize.…”
Section: Discussionmentioning
confidence: 99%
“…Note that although rhodopsin was detected in our mutant retinal sections, it may not indicate the presence of fully differentiated rods. Some authors have reported a rod/cone intermediate population, such "cods" have been recently characterized in retinal organoids from a NRL null patient showing an ESCS phenotype (Kallman et al, 2020). The observed phenotype of the D27 mutant could be the result of the short isoform overexpression plus the incapability of the long isoform to dimerize.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common methods to study the effect of key genes on retinal development is the use of genetically modified knocko murine models, which are frequently used to validate differentially expressed genes from microarray data. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Fluorescent gene reporter lines are widely used to check for gene expression in single cells, or purified populations of a single cell type. 2,[21][22][23][24][25] Bulk RNA sequencing (RNA-seq) has helped define the transcriptomes of larger populations of retinal cell types.…”
Section: Previous Methods In Vivo and In Vitromentioning
confidence: 99%
“…36,37 Single-cell RNA sequencing (scRNA-seq) is increasingly common today and is one the most detailed methods to profile transcriptomes of retinal cell types and subtypes. 2,8,13,22,[38][39][40][41][42][43][44][45][46][47][48] Most studies on retinal cell types have relied upon murine models, but many increasingly study human donor retinas 6,30,31,[48][49][50] , especially in order to profile retinal disease. 31,43,[50][51][52][53] Glaucoma, age-related macular dystrophy and retinal light damage have also been studied in murine models.…”
Section: Previous Methods In Vivo and In Vitromentioning
confidence: 99%
See 2 more Smart Citations